Zablokowany rozwój. Samoograniczenia ewolucji społeczeństwa obywatelskiego w Polsce = Blocked development: self-limitations of the evolution of civil society in Poland - Szczegóła, Lech (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article poses the problem of a "developmental crisis" of civil society in Poland. The first part describes three perspectives of the discourse on the condition of Polish civility and the criteria used in diagnosing it. In the second part, factors contributing to a sort of reproduction of blockades of its development - "maturing" are discussed. Conclusions concern the need for reflecting upon the stages of the evolution of the forms of civil society.
Keywords: społeczeństwo obywatelskie